Flame retardant transparent films of thermostable biopolyimide metal hybrids. (June 2021) - Phanthuwongpakdee, Jakkapon; Harimoto, Toyohiro; Babel, Sandhya; Dwivedi, Sumant; Takada, Kenji; Kaneko, Tatsuo
Highlights: Sugar-derived polyimide formed transparent films with metal ions through complexation. Biopolyimide metal hybrids possessed flame retardant properties. Biopolyimide metal hybrids retained thermal stability and mechanical strength. Abstract: The development of flame retardant transparent films is important for electric devices and building materials it but it is still a challenge. Herein, flame retardant films having high optical transparency were developed from the amino acid-based biopolyimide (BPI) salt with aluminum (BPI-COOAl) and copper ions (BPI-COOCu). The microscale combustion calorimetry analysis revealed that for BPI-COOAl, the total heat released ( THR ) and peak heat released rate were 4.5 W/g and 18.9 kJ/g, respectively. These values were lower than those of its precursors and BPI-COOCu. BPI-COOAl was rated V-0 for the Underwriters Laboratories vertical burning standard test. The polymer also retained a high transparency of more than 80% transmittance at a wavelength of 450 nm. The tensile strength was also preserved at 63.7 MPa. For BPI-COOCu, 14.6 kJ/g THR and 47.1 MPa tensile strength were observed. When a colorful ion such as Cu was used, BPI-COOCu became a flame retardant film that was a green filter. The char formation of Al₂O₃ and Cu₂O in their respective polymer complexes was deduced as the main flame suppression mechanism. The present films of biopolyimide salts are advantageous in showcasing the balance of different essential material properties such as flame retardancy, thermo-mechanical stability, and transparency.